1990
DOI: 10.1002/jts.2490030306
|View full text |Cite
|
Sign up to set email alerts
|

MMPI profiles and post‐traumatic symptomatology in former prisoners of war

Abstract: Results of this study found that prisoners of war (PO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…As in the earlier work, the scales that best differentiated the PTSD from non-PTSD subjects, and that produced the highest correlations with physiological responsivity to personal combat imagery, were those specifically designed to measure PTSD symptomatology (viz., the IOES and the Mississippi Scale for Combat-Related PTSD). The pattern of MMPI results obtained here in the largely non-POW, WWII and Korean War PTSD veteran subjects (i.e., elevations on Scales F, 1, 2, 3, 7, and 8) was similar to that previously reported in WWII and Korean POW subjects (Goldstein, van Kammen, Shelly, Miller, & van Kammen, 1987; Klonoff, Clark, Horgan, Kramer, & McDougall, 1976; Sperr, Sperr, Craft, & Boudewyns, 1990; Sutker & Allain, 1991; Sutker et al, 1991).…”
Section: Discussionsupporting
confidence: 87%
“…As in the earlier work, the scales that best differentiated the PTSD from non-PTSD subjects, and that produced the highest correlations with physiological responsivity to personal combat imagery, were those specifically designed to measure PTSD symptomatology (viz., the IOES and the Mississippi Scale for Combat-Related PTSD). The pattern of MMPI results obtained here in the largely non-POW, WWII and Korean War PTSD veteran subjects (i.e., elevations on Scales F, 1, 2, 3, 7, and 8) was similar to that previously reported in WWII and Korean POW subjects (Goldstein, van Kammen, Shelly, Miller, & van Kammen, 1987; Klonoff, Clark, Horgan, Kramer, & McDougall, 1976; Sperr, Sperr, Craft, & Boudewyns, 1990; Sutker & Allain, 1991; Sutker et al, 1991).…”
Section: Discussionsupporting
confidence: 87%
“…The authors suggested that age at the time of review of ptsd among elderlystudy may moderate PTSD leading to lower symptom levels among WWII veterans. Other studies have also documented a higher level of PTSD symptoms among younger versus older veterans (Sperr et al, 1990).…”
Section: Age Effectsmentioning
confidence: 97%